Reappraisal Reconsidered: A Closer Look at the Costs of an Acclaimed Emotion-Regulation Strategy. (April 2019) - Ford, Brett Q.; Troy, Allison S.
Cognitive reappraisal is a common form of emotion regulation that often centers on reframing how one thinks about an emotional situation so that one feels better. Given its demonstrated widespread benefits, two conclusions have been drawn about reappraisal: People can use it easily, and people should use it frequently. We critically examine these conclusions and highlight two fundamental drawbacks of reappraisal: First, people are often unable to use reappraisal successfully, and second, even when successful, using reappraisal to feel better is not always functional. To synthesize current research and inspire future research, we present a conceptual framework that systematically considers these drawbacks and how they may be influenced by individual-centered factors (e.g., the individual's skill) and situation-centered factors (e.g., a stressor's intensity) to shape outcomes across time. We then summarize the current literature and highlight the importance of considering reappraisal's costs and benefits in future research.